Left to right shunt congenital heart disease as a risk factor of recurrent pneumonia in under five-year-old children: a single centre experience in Bandung Indonesia - Sri Endah Rahayuningsih; Rahmat Budi Kuswiyanto; Filla Reviyani Suryaningrat; Heda Melinda Nataprawira; Abdurachman Sukadi (Medicinski glasnik, 2020)
Aim: Children with congenital heart diseases are at the greater risk of respiratory tract infection such as pneumonia. Recurrent pneumonia is one of the most major challenge for paediatric physicians. The aim of this study is to investigate risk factors of congenital heart diseases to recurrent pneumonia children. Methods: This was a retrospective study of under five-year-old children hospitalized in Hasan Sadikin General Hospital Bandung Indonesia from 2015 to 2018. Congenital heart diseases and pneumonia, as well as recurrent pneumonia, were identified. Congenital heart diseases diagnosis with and without pneumonia were reviewed. Results: Of 6997 hospitalized children, in 1258 (18.0%) congenital heart diseases were found, of which 232 (18.4%) had recurrent pneumonia. Most of those had left to right (L to R) shunt, 213 (91.8%). Congenital heart diseases in children aged under 1 year, 144 (62%) were more preponderant than in those aged 1-5 years. More than a half, 119 (51.3%) were males. Left to right shunt was documented as having recurrent pneumonia, of which patent ductus arteriosus and ventricular septal defect were the most common type in congenital heart diseases. Ventricular septal defect had a possibility for recurrent pneumonia by 1.551 times, and malnutrition 2.591 times. Conclusion: Ventricular septal defect and malnutrition were identified as risk factors for recurrent pneumonia. Those patients require multidisciplinary approach to prevent respiratory complications.
Keywords: cardiac defect; child; complication; heart murmur; ventricular septal defect